Pemanfaatan Limbah Padi pada Civitas SMK Pertanian Pembangunan Negeri Padang, Sumatera Barat - Anwar Kasim; Annisa Putri (Warta Pengabdian Andalas, 2023)
The rice production process produces a by-product called rice agricultural waste, namely rice straw. Rice straws in huge quantities can be used to manufacture various products such as paper, art paper, decor boards, and paintings. Processing rice straw waste can increase the value-selling of the product and reduce environmental pollution. Rice straw can be found in Padang City, especially around the location of the Padang State Development Agricultural Vocational High School. It causes the buildup of rice straw waste at several points around the school. This activity aimed to provide knowledge to the students regarding using rice straw waste as valuable products. The method was counselling and training the students. The results of this activity showed their high enthusiasm for producing paper products, decorative boards, and paintings from rice straw waste.